Effect of Microscopic Pore Throat Structure on Displacement Characteristics of Lacustrine Low Permeability Sandstone: A Case Study of Chang 6 Reservoir in Wuqi Oilfield, Ordos Basin - Ren Qiang; Wei Hu; Lei Guofa; Zhang Weigang; Ge Bingyu; Nan Junxiang (Geofluids)
Pore throat structure is the key factor affecting displacement efficiency in low permeability reservoirs. In this paper, the pore throat structure and displacement characteristics of Chang 6 low permeability sandstone reservoir in Wuqi area of Ordos Basin were studied by casting thin section analysis, scanning electron microscopy, XRD, high-pressure mercury injection, and microscopic displacement model of real sandstone test. The results show that the size and homogeneity of the pore throat structure deteriorate gradually from type I to type IV reservoir, and the corresponding displacement efficiency also decreases gradually. The type I reservoir is dominated by uniform displacement, and residual oil is dominated by oil film. Type II reservoir is dominated by mesh and finger displacement, while type III reservoir is dominated by finger displacement, and continuous remaining oil distribution is easy to be formed after water flooding. Pore throat size and homogeneity are important factors affecting oil displacement efficiency. The larger the pore throat size, the more homogeneous the structure, and the stronger the seepage capacity, the higher the oil displacement efficiency. With the increase of volume displacement multiple, the displacement efficiency growth rate of the type I reservoir changes little, while the displacement efficiency growth rate of the type II and type III reservoir decreases gradually. In actual production and development, reasonable control of pressure is the key to dependable production.